A quarta onda do movimento feminista: o fenômeno do ativismo digital - Rocha, Fernanda de Brito Mota (Universidade do Vale do Rio dos Sinos, 2017)
The present dissertation contemplated the study of the Fourth Wave of the Feminist Social Movement, justifying itself in the face of the social changes provoked by information technology in promoting and disseminating the ideals that constitute this facet of the Movement. Focusing on the action of feminism on the internet, specifically addressed the collection of data from a feminist blog. As a general objective, the aim was to analyze the configuration of the feminist movement in the specificity of digital activism, its proposals for discussion and timelines opportunized via technological tools, specifically the internet, in the process of dissemination of the feminist struggle for the expansion of rights. It was chosen to check one year of posting of the blog “Escreva Lola Escreva” and select, each month, the posts with the highest number of comments to later make an analysis of the topics discussed. This methodological choice is based on the fact that the most commented posts have generated greater discussion and interest. It was not the purpose of this research to analyze the comments. They served as criteria for corpus selection. Considering the results pointed out by data analysis performed without documentary corpus, what draws attention is an interaction of readers as active subjects and possible changes of opinion and ways of facing life, from those interactions. It is highlighted as a recurrent category the critique of patriarchy in several perspectives. It reinforces the idea of the critical perception of the oppressive system, centered in men. Considering the empirical analysis and based on the literature, one can affirm the existence of the Fourth Wave of the Feminist Movement, characterized by digital activism. By presenting and opportuning the discussions and guidelines experienced in the social sphere, it testifies that digital social movements are gaining space and representativeness.
Keywords: Ciberativismo; Ciberfeminismo; Quarta onda do movimento social feminista; Ciberativism; Cyberfeminism; Fourth wave of the feminist social movement; ACCNPQ::Ciências Humanas::Sociologia